POSITIONING IDEOLOGI PARTAI POLITIK PADA PREFERENSI POLITIK SANTRI - Bariroh, Laili (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This study is conducted based on the weaknesses of political parties. It is questioning the ideology of political parties which tends to be less operational, undemocratic and – to some extent – centralized management, and the absence of accountability. Using qualitative approach, the study findsthat there are two main typologies, according to santri (students of Islamic boarding schools), namely pragmatic parties and parties of interests. Moreover, related to the positioning of the ideology of political parties,based onstudents’ preferences, the students grounded their information on mass media and social media. Moreover, ideology and value system are not important aspects adopted by the students in their political preferences. To them politicians are merely groundless political actorswho put less effort to fight for the sake of people’s interests. In addition, the students argue that politicians put most emphasis merely on their party and themselves.